Feeling in Responding Advertising Exposure on YouTube: The Moderation Influence of Online Experience - Tri Weda Raharjo (Türkiye İletişim Araştırmaları Dergisi, 2019)
The use of YouTube as a medium of social networking to promote the products proved to be quite effective, yet sometimes it can cause disruption to the users. It is due to the advertisement has interrupted the streaming activity, causing annoyance and displeasure followed by avoidance. Regarding with the problem, this study examined the feelings while response to ad impressions on YouTube. The population of the study is including the YouTube users in Indonesia. Questionnaires used for collecting data which is involving 105 samples of 263 samples that had been spread on colleges and government offices in Surabaya. From the results of this study, it can be concluded that: (1) ad intrusiveness significantly affect ad irritation; (2) online experience does not significantly provide impact in weakening the relation among ad intrusiveness and ad irritation; (3) online experience significantly impact on weakening the relation among ad intrusiveness and ad avoidance; (4) ad intrusiveness significantly affect ad avoidance; (5) ad irritation significantly affect ad avoidance; (6) ad avoidance does not significantly affect the attitude toward the brand.